Commodity Markets Outlook, October 2015 - World Bank Group (World Bank, Washington, DC, 2015)
Ample supplies and weak demand, especially for industrial commodities, contributed to the continued slide in most commodity prices in the third quarter of 2015. Annual price forecasts are revised down for 2015 and 2016. Only a modest recovery is expected in 2016. This issue briefly analyzes the implications of the ongoing El Niño episode and the recent Nuclear Agreement with Iran for agricultural and energy markets, respectively. Although El Niño could be the strongest on record, its impact is likely to be predominantly local rather than global because world commodity markets are currently well supplied and spillovers from local markets to global prices are typically weak. Following Iran’s Nuclear Agreement, the country’s 40 million barrels in floating storage could be made available almost immediately upon sanctions being lifted; and, within a few months, Iran could increase its crude oil production toward pre-sanctions levels. The impact of Iranian exports on global oil and natural gas markets could be large over the longer term provided that Iran attracts the necessary foreign investment and technology to extract its substantial reserves.